2022
DOI: 10.1021/acsptsci.2c00026
|View full text |Cite
|
Sign up to set email alerts
|

Hit Expansion of a Noncovalent SARS-CoV-2 Main Protease Inhibitor

Abstract: Inhibition of the SARS-CoV-2 main protease (M pro ) is a major focus of drug discovery efforts against COVID-19. Here we report a hit expansion of non-covalent inhibitors of M pro . Starting from a recently discovered scaffold (The COVID Moonshot Consortium. Open Science Discovery of Oral Non-Covalent SARS-CoV-2 Main Protease Inhibitor Therapeutics. bioRxiv 2020.10.29.339317) represented by an isoquinoline series, we searched a database of over a billion compounds using a cheminformatics molecular fingerprinti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Six compounds presented inhibitory effects against 3CL pro both in vitro and in HEK293T cells, and Z1759961356 hindered viral replication in Vero E6 cells with an EC 50 value of 8.52 μM. Four isoquinolone‐based compounds from a database were reported as SARS‐CoV‐2 3CL pro inhibitors with IC 50 values of approximately 1 μM 137 …”
Section: Synthetic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six compounds presented inhibitory effects against 3CL pro both in vitro and in HEK293T cells, and Z1759961356 hindered viral replication in Vero E6 cells with an EC 50 value of 8.52 μM. Four isoquinolone‐based compounds from a database were reported as SARS‐CoV‐2 3CL pro inhibitors with IC 50 values of approximately 1 μM 137 …”
Section: Synthetic Compoundsmentioning
confidence: 99%
“…Four isoquinolone-based compounds from a database were reported as SARS-CoV-2 3CL pro inhibitors with IC 50 values of approximately 1 μM. 137 In fact, some inhibitors have a potential impact on several 3CL pro s due to the high conservation of this protease among CoVs. 138 For example, ML188 inhibited the 3CL pro of SARS-CoV, SARS-CoV-2, and porcine epidemic diarrhea virus, making it a promising broad-spectrum antiviral agent.…”
Section: Non-peptidomimetic Sars-cov-2 3cl Pro Inhibitorsmentioning
confidence: 99%
“…And this was only achieved following many iterations of structure-based design, synthesis and assays of analogues [78,81,82]. Also of concern, a subsequent virtual hit expansion/ligandbased screening starting with the isoquinoline-bearing inhibitors such as 6 and using the Ukrainian REAL database which contains 1.37 billion of compounds, actually failed to go beyond this chemical motif [83]. In any case, what would have been the results of all these computer-based endeavors had the hits 4 and 5, which led to compounds 6 and 7, not been reported [79,80] in 2013?…”
Section: Perspective Hit Discovery Frequent Hitters and Virtual Scree...mentioning
confidence: 99%
“… 3 , 4 In structural evaluations to find anti-COVID-19 agents, quinoline and isoquinoline scaffolds are among the most important platforms that have been repeatedly observed in the structure of potent SARS-CoV-2 inhibitors. 5 , 6 Emetine, which itself has two isoquinoline-like moieties, is the main pharmacologically active alkaloid in ipecac root that was previously used in traditional medicine and clinics as an expectorant, emetic, and anti-amoebic agent, and it has been approved by competent authorities such as the U.S. Food and Drug Administration (FDA) for clinical usages. In addition to the mentioned drug effects, studies reported some other important biological activities for this compound, such as inhibition of protein synthesis 7 , 8 and anti-cancer effects.…”
mentioning
confidence: 99%
“…Today, naturally occurring compounds are receiving increasing attention for the treatment of diseases (such as COVID-19) because they offer a diversity of biological activities and low toxicity. , In structural evaluations to find anti-COVID-19 agents, quinoline and isoquinoline scaffolds are among the most important platforms that have been repeatedly observed in the structure of potent SARS-CoV-2 inhibitors. , Emetine, which itself has two isoquinoline-like moieties, is the main pharmacologically active alkaloid in ipecac root that was previously used in traditional medicine and clinics as an expectorant, emetic, and anti-amoebic agent, and it has been approved by competent authorities such as the U.S. Food and Drug Administration (FDA) for clinical usages. In addition to the mentioned drug effects, studies reported some other important biological activities for this compound, such as inhibition of protein synthesis , and anti-cancer effects. This compound also has excellent broad-spectrum antiviral effects against a wide range of RNA and DNA viruses at a non-cytotoxic concentration, without causing drug resistance .…”
mentioning
confidence: 99%